Digital technology for health shows disparities in cancer prevention between digital health technology users and the general population in Romania - Pana, Bogdan C.; Ciufu, Nicolae; Ciufu, Carmen; Furtunescu, Florentina L.; Turcu-Stiolica, Adina; Mazilu, Laura (Frontiers in Oncology, 2023)
Introduction Digital health services and technology are rapidly developing following the COVID-19 pandemic. This study aimed to reveal the differences between users of digital health technology (DHT) and the general population with regard to cancer prevention. Materials and Methods This was an observational study on a conventional sample of 270 DHT users with completed data, performed in September 2021. Results A significant difference was observed in the proportion of DHT users and the general population reporting the screening test results, which was 2–6 times higher in the DHT group. Digital technologies applied to the “self-care” model were more suitable for internet-literate populations. Discussion Including digital technologies in a self-care model may be more suitable for internet-literate individuals. Thus, in a preventative health organizational framework, DHT should be integrated and used at the primary care level in the general population to improve disparities in the preventative health domain.